English Communication Challenges Faced by Bellboys During Group Check-In and Check-Out Processes at Lovina Beach Club & Resort - Made Yudistira Wijaya; Anak Agung Sri Barustyawati; I Made Suta Paramarta (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Effective communication is an essential aspect of hospitality services, particularly for bellboys who interact directly with international guests during group check-in and check-out processes. However, communication with guests from different linguistic and cultural backgrounds may create various challenges that affect service effectiveness. Therefore, this study aimed to identify the English communication challenges encountered by bellboys during group check-in and check-out processes at Lovina Beach Club & Resort. This study employed a descriptive qualitative research design. Data were collected through non-participant observation using an observation checklist and semi-structured interviews involving two bellboys who had direct experience in handling international group guests. The collected data were analyzed through transcription, coding, categorization, and interpretation to identify recurring patterns of communication challenges. The findings revealed five major English communication challenges, namely limited English proficiency, accent and pronunciation differences, ambiguity in guest messages, cultural differences, and environmental challenges such as crowded situations and noise during group guest handling. These challenges were influenced by both linguistic factors and operational conditions in the hospitality setting. The study concludes that effective communication in hospitality depends not only on English language proficiency but also on the ability of bellboys to adapt their communication to different guest characteristics and service situations.